Rape, Sexual Abuse Investigation and the Use of DNA Evidence in the Northern Cape, South Africa - Mabunda, Dumisani Quiet (Journal of Law, Society and Development, 2025)
Gender-based crimes such as rape and abuse have increased exponentially, as shown in the quarterly South African Police Service (SAPS) crime statistics. In Northern Cape, in particular, these crimes seem to be increasing rapidly, and socio-economic factors such as high unemployment and substance abuse seem to be the main contributing factors. Crime statistics from the last quarter of 2023 showed that 103 sexual offences were reported. This represents 1.4% of the overall reported sexual offences in South Africa. These statistics are very concerning and require police to develop novel strategies to stop rape and sexual abuse. The number of unsuccessful prosecutions due to lack of or insufficient evidence such as Deoxyribonucleic Acid (DNA) is particularly worrying. A qualitative research approach including the phenomenological research design were adopted during research for this article. Fifty-five (55) participants) were purposively sampled. In addition, unstructured key informant interviews (KIIs) and focus group discussion (FGDs) were adopted for data collection. The collected data were analysed using inductive Thematic Content Analysis (TCA). This article focuses on the effective use of DNA evidence during the investigation process of sexual offences in Northern Cape, South Africa. It also highlights the importance of incorporating DNA evidence to improve the accuracy and efficiency of sexual crimes investigations. The article also seeks to explore the significance of DNA analysis in the investigation of sexual assault crime.